Europas plantage? Afrikas plats i EU:s historia - Hansen, Peo; Jonsson, Stefan (K&K - Kultur og Klasse, 2015)
This essay describes the history of the Eurafrican project as it evolved from the Pan-European movement in the 1920s to its institutionalization in the European Economic Community (i.e. today’s EU) in the late 1950s. By way of conclusion, the article also discusses how this history affects current relations between Africa and the EU. As shown in the article practically all of the visions, movements and concrete institutional arrangements working towards European integration during this period placed Africa’s incorporation into the European enterprise as a central objective. European integration, it is argued, was thus inextricably bound up with a Eurafrican project. According to the geopolitical discourse on Eurafrica that became politically operative in the aftermath of World War II, a future European community presupposed the transformation of the strictly national colonial projects into a joint European colonization of Africa. Indeed, there is strong evidence to support that these ideas were instrumental in the actual, diplomatic and political constitution of the EU, or of Europe as a political subject. As the article shows, the history of Eurafrica, which is largely ignored in scholarship on the EU as well as in colonial studies, cannot be understood within a “continentalist” framework, but prompts a reconceptualization of the historical relation Africa and Europe.